A Highly Stable Nonhysteretic {Cu2(tebpz) MOF+water} Molecular Spring1. Issue 21 (9th September 2016) - Grosu, Yaroslav; Li, Mian; Peng, Yun‐Lei; Luo, Dong; Li, Dan; Faik, Abdessamad; Nedelec, Jean‐Marie; Grolier, Jean‐Pierre
Abstract: A molecular spring formed by a hydrophobic metal–organic framework Cu2 (tebpz) (tebpz=3, 3′, 5, 5′‐tetraethyl‐4, 4′‐bipyrazolate) and water is presented. This nanoporous heterogeneous lyophobic system (HLS) has exceptional properties compared to numerous reported systems of such type in terms of stability, efficiency, and operating pressure. Mechanical and thermal energetic characteristics as well as stability of the system are discussed and compared in detail with those of other previously reported HLS. Abstract : Spring loaded : A molecular spring (MS) system formed by a highly hydrophobic metal–organic framework (MOF) and water (see figure) with exceptional stability, efficiency, and operating pressure is reported. This is the first MS having such a combination of properties and the first nonhysteretic MOF‐based heterogeneous lyophobic system. Mechanical and thermal characteristics of the MS are presented.